Progress in Studying Salt Secretion from the Salt Glands in Recretohalophytes: How Do Plants Secrete Salt? - Yuan, Fang; Leng, Bingying; Wang, Baoshan (Frontiers in Plant Science, 2016)
To survive in a saline environment, halophytes have evolved many strategies to resist salt stress. The salt glands of recretohalophytes are exceptional features for directly secreting salt out of a plant. Knowledge of the pathway(s) of salt secretion in relation to the function of salt glands may help us to change the salt-tolerance of crops and to cultivate the extensive saline lands that are available. Recently, ultrastructural studies of salt glands and the mechanism of salt secretion, particularly the candidate genes involved in salt secretion, have been illustrated in detail. In this review, we summarize current researches on salt gland structure, salt secretion mechanism and candidate genes involved, and provide an overview of the salt secretion pathway and the asymmetric ion transport of the salt gland. A new model recretohalophyte is also proposed.